The ecological business vision in social responsibility and sustainable marketing in the tourism sector (Revista de Investigaciones Universidad del Quindío, 2021)
The objective of the research was to evaluate the business ecological vision of tourism service providers formed by business ecological planning and investment in ecology; and its relationship with social responsibility and sustainable marketing.The non-experimental quantitative method was chosen with an inferential multivariate statistical analysis, using the Multiple Linear Regression model for the acceptance or rejection of the research hypotheses. The sample was random probabilistic, stratified, made up of tourist service providers from the destination of “Bahías de Huatulco”, in Oaxaca and in the Municipality of “Guaymas”, Sonora at Mexico.It is concluded that by working from the top management with an ecological business vision, it will have a positive impact on Social Responsibility and on the sustainable marketing of companies that provide tourist services.
Keywords: Business Ecological Vision; Social Responsibility; Sustainable Marketing